Aging with quality of life the perception of the participants of the Universidade da Criativa Idade Program (Citizenship in Action: Extension and Culture Magazine, 2023)
Due to the expansion of its life expectancy, the elderly population has grown significantly in recent years and therefore the concept of aging has received a more careful and attentive look, considering that the elderly need activities that improve their balance, memory, social interaction and emotional state. In this context, extension activities, such as the University of Creative Age Extension Program, address these issues through group activities, of a physical, artisanal and intellectual nature. Seeking to evaluate the presence of the program in the participants' lives, through the case study methodology, through a descriptive study, of the experience report type, this work aimed to evaluate the influence of the Universidade da Criatividade Extension Program in the quality of participants' lives. Taken together, the results demonstrate that the program has positively influenced the participants' quality of life, providing new information, knowledge, increased self-esteem, willingness to go about their daily lives, self-knowledge, new ways of relating and seeing health and health. the quality of life.
Keywords: University of the Creative Age; university extension; healthy aging; quality of life